Long-Term Follow-Up Results of a Second-Generation Cementless Femoral Prosthesis with a Collar and Straight Distal Fixation Channels - Han, Chang Wook; Yang, Ick Hwan; Lee, Hye Yeon; Han, Chang Dong (Yonsei medical journal, 2012)
We evaluated the results of more than 10 years of follow-up of total hip arthroplasty using a second-generation cementless femoral prosthesis with a collar and straight distal fixation channels. One hundred five patients (129 hips) who underwent surgery between 1991 and 1996 for primary total hip arthroplasty using cementless straight distal fluted femoral stems were followed for more than 10 years. Ninety-four hips in 80 patients were available for clinical and radiologic analysis. The mean age at the time of surgery was 47 years, and the mean duration of follow-up was 14.3 years. The mean Harris hip scores had improved from 58 points to 88 points at the time of the 10-year follow-up. Activity-related thigh pain was reported in nine hips (10%). At the last follow-up, 93 stems (99%) were biologically stable and one stem (1%) was revised because of loosening. No hip had distal diaphyseal osteolysis. Proximal femoral stress-shielding was reported in 86 hips (91%). We found no significant relationship between collar-calcar contact and thigh pain, stem fixation status, or stress-shielding. The cumulative survival of the femoral stem was 99% (95% confidence interval, 98-100%) after 10 years. The long-term results of total hip arthroplasty using a second-generation cementless femoral prosthesis with a collar and straight distal fixation channels were satisfactory; however, the high rate of proximal stress-shielding and the minimal effect of the collar indicate the need for some changes in the stem design.